Ramipril Alleviates Oxaliplatin-Induced Acute Pain Syndrome in Mice - Bouchenaki, Hichem; Danigo, Aurore; Bernard, Amandine; Bessaguet, Flavien; Richard, Laurence; Sturtz, Franck; Balayssac, David; Magy, Laurent; Demiot, Claire (Frontiers in Pharmacology, 2021)
Oxaliplatin (OXP) is a key drug for colorectal cancer that causes OXP induced peripheral neuropathy, a dose‐limiting effect characterized by cold and tactile hyperesthesia. The relationship between the sensory nervous system and modulation of the renin-angiotensin system (RAS) has been described, focusing on pain and neurodegeneration in several animal models. We assessed the effect of the RAS modulator, ramipril (RAM), an angiotensin converting-enzyme inhibitor in a mouse model of OXP-induced acute pain syndrome (OIAS). OXP was administered in Swiss mice at a cumulative dose of 15 mg/kg (3 x 5 mg/kg/3d, i.p.). RAM was administered i.p. every day from 24 h before the first OXP injection until the end of the experiments. We evaluated OIAS development and treatment effects by sensorimotor tests, intraepidermal nerve fiber and dorsal root ganglia-neuron immunohistochemical analyses, and sciatic nerve ultrastructural analysis. OXP-treated mice showed tactile allodynia and cold hypersensitivity, without motor impairment and evidence of nerve degeneration. RAM prevented cold sensitivity and improved recovery of normal tactile sensitivity in OXP-treated mice. Our finding that RAM alleviates OXP-induced pain is a step towards evaluating its therapeutic potential in patients receiving OXP treatment.